Hypoacetylation of acetyl‐histone H3 (H3K9ac) as marker of poor prognosis in oral cancer. Issue 2 (23rd May 2017) - Webber, Liana P; Wagner, Vivian P; Curra, Marina; Vargas, Pablo A; Meurer, Luise; Carrard, Vinícius C; Squarize, Cristiane H; Castilho, Rogério M; Martins, Manoela D
Abstract : Aims: Epigenetics refers to changes in cell characteristics that occur independently of modifications to the DNA sequence. Oral carcinogenesis is influenced by modifications in epigenetic mechanisms, including changes in histones, which are proteins that support chromatin remodelling for the dynamic regulation of gene expression and silencing. The dysregulation of histone acetylation can lead to the uncontrolled activity of different genes, thereby triggering events associated with malignant transformation. The aim of this study was to analyse the expression of acetyl‐histone H3 at lys9 (H3K9ac) in oral leucoplakia (OL) and oral squamous cell carcinoma (OSCC) in addition to its association with cell proliferation, epithelial–mesenchymal transition (EMT) and clinical‐pathological findings. Methods and results: Samples of normal oral mucosa (NOM), OL and OSCC were submitted to immunohistochemical analysis using anti‐H3K9ac, Ki67 and vimentin. Slides were submitted to quantitative analysis regarding the percentage of positive cells. OSCC presented less expression of H3K9ac in comparison to OL ( P < 0.01), whereas Ki67 and vimentin levels increased from OL to OSCC ( P < 0.001 and P = 0.03, respectively). OSCC patients with poor prognosis had less H3K9ac expression ( P = 0.04). The Kaplan–Meier cumulative survival curves also revealed lower survival rates in patients with less H3K9ac expression ( P < 0.01). Conclusions: The present findings suggest that changes in H3K9ac occur during the process of oral carcinogenesis along with an increase in cell proliferation and EMT. The results demonstrate that H3K9ac may be a useful novel prognostic marker for OSCC.